ORGANIZATION OF MOBILE GAMES IN THE SUMMER CAMP OF THE REHABILITATION CENTER - Alexandra Vorozhbitova; Ekaterina Tyutina; Natalia Pryadko (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the analysis of the current state of knowledge of this type of adaptive motor recreation (ADR), the peculiarities of the organization of the ADR at summer camp rehabilitation centre. Given the scientific-methodical bases of the organization of outdoor games depending on the limitations of health tourists, their age peculiarities and character.